St. La Salle award - Laudico, Minerva (Animo Repository, 1989)
In schoolyear 1989-1990, the St. La Salle award was given to Dr. Minerva Laudico, Vice President at Centro Escolar University, for her achievements as a Christian educator, social worker and leader in women's development. The award was given during the feast day of St. John Baptist de la Salle.